Impact of Age and Ethnic Variability on Cardiovascular Risk in Chronic Kidney Disease Patients - Saif Ullah Shaikh, Afsheen Zehra, Areeb Arif Khan, Habib Saghir, Muhammad Saeed, Muhammad Faisal Fahim (Journal of Islamic International Medical College)
Objective: To investigate the effect of age and ethnicity on cardiovascular disease risk in patients with chronic kidney disease. Study Design: Descriptive Cross-sectional. Place and Duration of Study: This study was conducted at the Department of Nephrology, Jinnah Post Graduate Medical Centre and Cantonment board Clifton health care center, Karachi from 21st August 2023 to 21st February 2024. Materials and Methods: One- forty male and female chronic kidney disease (CKD) patients aged 25–60 with diabetes and hypertension for at least five years were included. Patients on renal replacement therapy with coronary artery disease, liver disease, hormonal or steroidal medicine, pregnancy, or breastfeeding were excluded. Descriptive statistics employed mean for quantitative variables. The demographics and case history of patients were collected on a performa and grouped by ethnicity. BMI, Hb, creatinine, urea, lipid profile, and BNP were measured. Quantitative variables were shown. Data was analyzed using SPSS version 25.0. Statistical analysis included Pearson correlation test and One-way Anova to compare the biochemical parameters across the different groups. Results: In CKD patients, age was positively linked with Hb% (P = 0.018), serum urea (P = 0.000), serum creatinine (P = 0.000), total cholesterol (P = 0.002), and LDL- Cholesterol (P = 0.024). Pathans had significantly higher total cholesterol levels (171.53± 39.75) with a P-value of 0.019. Sindhi had the highest HDL- cholesterol levels (mean 54.44 ±6.48) with a significant P-value < 0.001. Gilgiti had the highest BNP levels (307.37± 57.71) with a significant P-value< 0.0001. Conclusion: The study found that age and ethnicity affect CKD-related CVD. Adding these traits to clinical practice should improve high-risk CKD screening and management. By closing demographic gaps and customizing treatments, clinicians can lower CVD risk and CKD consequences.